2019
DOI: 10.1249/mss.0000000000001942
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Injurious Falls, and Physical Function in Aging: An Umbrella Review

Abstract: Purpose: To review and update the evidence of the relationship between physical activity, risk of fall-related injury, and physical function in community-dwelling older people that was presented in the 2018 Physical Activity Guidelines Advisory Committee Scientific Report (PAGAC Report). Methods: Duplicate independent screenings of 1,415 systematic reviews and meta-analyses published between 2006 and 2016 identified from PubMed®, Cochrane Library, and CINAHL databases yielded 111 articles used for the PAGAC Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
146
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(168 citation statements)
references
References 56 publications
11
146
1
10
Order By: Relevance
“…Consistent with those of previous studies [6,[25][26][27] indicating that meeting physical activity recommendation can help to improve or delay the loss of physical function in older adults, our results further extend previous ndings by demonstrating that achieving the recommended minimum level of step-based physical activity (7,000 steps/day) is also protective for older adults against lower-extremity functional decline. Our ndings can be explained by a number of previous laboratory-based trials, which demonstrated that accumulating a certain amount of physical activity in short bouts has the same health bene ts as engaging in the same overall amount of activity in a single continuous period in terms several health indicators [28][29][30][31].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with those of previous studies [6,[25][26][27] indicating that meeting physical activity recommendation can help to improve or delay the loss of physical function in older adults, our results further extend previous ndings by demonstrating that achieving the recommended minimum level of step-based physical activity (7,000 steps/day) is also protective for older adults against lower-extremity functional decline. Our ndings can be explained by a number of previous laboratory-based trials, which demonstrated that accumulating a certain amount of physical activity in short bouts has the same health bene ts as engaging in the same overall amount of activity in a single continuous period in terms several health indicators [28][29][30][31].…”
Section: Discussionsupporting
confidence: 92%
“…The study found that after six and 12 weeks of intervention, the API group achieved higher improvement on fall risk score as compared to the NPI group. Previous studies have found that the effect of OLPI, such as Tai-Chi, on fall risk was promising but inconclusive (50)(51)(52)(53). The current study results are in accordance with previous publication (33) suggest that the Ai-Chi method can help to reduce fall risk.…”
Section: Discussionsupporting
confidence: 89%
“…7 Physical activity has been shown to be a very effective strategy in the prevention and treatment of DM2, with similar benefits from both endurance and strength training on insulin sensitivity and glycemic control, 8 increased fitness levels, 9 and decreased risk of disability. 10 Moreover, strength training focusing on performing the concentric phase of the movement as fast as possible has been shown to improve physical performance in DM2 frail older people. 11 The Supplement provides a simple, well-structured multicomponent training program that older DM2 adults could follow at home.…”
mentioning
confidence: 99%
“…The exercise protocol has been developed to maintain muscle mass, strength, and therefore glycemic control and functional ability. 7,10 Other important aspects like mobility, flexibility, and balance are also included. In general, this training program is suitable for older adults without severe mobility and/or balance limitations, as well as other medical conditions that would prevent them from performing exercises using high movement velocities (ie, recent hip fractures, stroke).…”
mentioning
confidence: 99%
See 1 more Smart Citation